Time and space in reading – the interplay between pleasure and comprehension in a reading task - Vilson Jose Leffa (Ilha do Desterro)
This paper investigates the correlation between comprehension and pleasure in a reading task. While comprehension is defined here within a spatial dimension, including the reader’s ability to relate the text being read to other texts, pleasure is seen as the reader’s reaction to the text, in a more temporal perspective. To test the hypotheses that there is a positive correlation between them, 67 students from 5th grade to university level were asked to read a text and answer a comprehension/reaction questionnaire. The results showed that there is a positive correlation between comprehension and pleasure. Aspects involving intertextuality, interest and previous knowledge are also discussed.